Dampak Keberadaan Grand Mall Batangase Terhadap Tingkat Pendapatan Pedagang Pasar Tradisional Batangase Kabupaten Maros - Andarina, Rezki (UNIVERSITAS NEGERI MAKASSAR, 2019)
This study aims to determine: (1) The description of the traditional market traders income before the Grand Mall, (2) description of the traditional market traders income after their Grand Mall, (3) The impact of the Grand Mall to the traditional market traders income levels. The method used is descriptive quantitative and population in this study is the traditional market traders who sell similar goods with the goods sold in the Grand Mall as many as 288 vendors. The sample was 72 merchants. Data collection techniques by observation, interviews, questionnaires / questioner and documentation with the relevant parties. Methods of data analysis used descriptive analysis. The results showed that the presence of the Grand Mall impact on traditional market traders. As for the impact that revenue diminution, reduction in the number of customers, decreasing the amount of sales of goods. Based on the 72 traders only 23 were affected and the remaining 49 traditional traders are not affected by the presence of the modern market. So that, when viewed descriptively in fact the presence of the Grand Mall is not as strong an effect on the income of traditional market traders batangase only affect 23 traders from 72 traditional traders as samples, or approximately 32%.